The endoplasmic reticulum: protein folding and control of calcium homeostasis - Michalak, Marek (Henry Stewart Talks, 2007)
Quality control, Chaperones and folding enzymes in the ER, Prevention of the deployment of misfolded proteins, Impaired protein folding in Alzheimer's disease, CMT and cystic fibrosis, Deficiency in ER calcium-binding chaperones impacts embryonic development, The lymphatic drainage system of the brain, The gut-immune-brain axis, Exercise, immunity, and mental health, Gut microbiome, Update talk: ER stress, Update talk: The Unfolded Protein Response (UPR), Update talk: ER stress sensors, Update talk: Inositol-Requiring Element 1 (IRE1α), Update talk: Stress-induced activation of the calreticulin gene, Update talk: Targeting IRE1α to prevent cardiac fibrosis, Update talk: TUDCA prevents cardiac fibrosis
Updated at 2022/01/30